Islamic Caliphate or nation state? Investigating the Islamic State of Iraq and the Levant's imagined community. Issue 3 (12th June 2020) - Caló, Ben; Malet, David; Howie, Luke; Lentini, Pete
Abstract: Through the lens of Benedict Anderson's Imagined Community concept, this paper examines how the selected community‐building theories are useful in understanding the Islamic State of Iraq and the Levant (ISIL) and its imagined community. Using four factors— language, education, power and history —derived from Anderson's Imagined Community concept, this paper applies theories of Modernism, Primordialism and Insurgency Governance to explain ISIL's imagined community. Specifically, our argument is threefold: (a) Anderson's Imagined Community concept and alternate theories of community building, although insightful, does an imperfect job at describing ISIL's Caliphate; (b) ISIL's group structure appears to transcend traditional and accepted notions of nations, nationalism and nation states; and (c) based on this reasoning, ISIL's Caliphate can be considered an outlier in community‐building literature analysed.